The death of prehistory - Schmidt, Peter R. (Peter Ridgway) 1942-; Mrozowski, Stephen A. (Oxford University Press, 2013)
This volume provides examples of how the concept of prehistory has diminished histories of other cultures outside the West and how archaeologists can reclaim more inclusive histories set within the idiom of deep histories - accepting ancient pre-literate histories as an integral part of the flow of human history.